2022
DOI: 10.2147/opth.s353787
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing of Inherited Retinal Disease in Australian Private Tertiary Ophthalmology Practice

Abstract: Background To assess the prevalence of genetic testing for inherited retinal diseases (IRDs) in a tertiary practice setting. Methods Single-centre retrospective analysis of patients with diagnosed or suspected IRD. Results Four hundred and sixty-four patient records were analysed. Patients had received care for different IRDs grouped as follows: panretinal pigmentary retinopathies (283, 61%), macular dystrophies (136, 29.3%), stationary disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…Similarly, in the study by Choi et al, only 10% of carriers of a wide range of X‐linked conditions reported they had sufficient access to knowledgeable healthcare providers exploring symptoms and/or the risks associated with being a carrier 8 . Insufficient counselling was also evident through an audit of a private tertiary ophthalmology practice in Australia, whereby approximately 70% of clinical records did not document any counselling provided to patients with an IRD 20 . Whether this is due to clinical record documentation inaccuracies or is indicative of an area for improvement for clinicians remains unknown.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, in the study by Choi et al, only 10% of carriers of a wide range of X‐linked conditions reported they had sufficient access to knowledgeable healthcare providers exploring symptoms and/or the risks associated with being a carrier 8 . Insufficient counselling was also evident through an audit of a private tertiary ophthalmology practice in Australia, whereby approximately 70% of clinical records did not document any counselling provided to patients with an IRD 20 . Whether this is due to clinical record documentation inaccuracies or is indicative of an area for improvement for clinicians remains unknown.…”
Section: Discussionmentioning
confidence: 98%
“…8 Insufficient counselling was also evident through an audit of a private tertiary ophthalmology practice in Australia, whereby approximately 70% of clinical records did not document any counselling provided to patients with an IRD. 20 Whether this is due to clinical record documentation inaccuracies or is indicative of an area for improvement for clinicians remains unknown. However, considering that 25% of carriers reported that their clinician was no help to them, there is a demand for better counselling practices by clinicians.…”
Section: Female Carriers' Genetic Testing Experiencesmentioning
confidence: 99%
“…While open‐access genetic testing programs, such as the My Retina Tracker 39 and ID YOUR IRD 40 programs in the United States, have made genetic testing more accessible in some countries, these programs have not been available in Australia until recently. A recent review of an Australian private tertiary ophthalmology practice found that genetic testing results were only available for 9.5% of 464 patient records audited 41 . Since July 2021, VENTURE participants have had access to molecular testing through sponsored testing programs, which provide a comprehensive and efficient analysis of multiple genes associated with IRDs 42 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of an Australian private tertiary ophthalmology practice found that genetic testing results were only available for 9.5% of 464 patient records audited. 41 Since July 2021, VENTURE participants have had access to molecular testing through sponsored testing programs, which provide a comprehensive and efficient analysis of multiple genes associated with IRDs. 42 Through these programs, all VENTURE registrants have been offered the opportunity to have targeted panel testing to screen for known variants if they have not previously received a molecular diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Pre‐testing counselling is important for ensuring that patients are prepared for the implications of the results 9 . The uptake of IRD genetic testing in Australian private ophthalmology clinics is currently estimated to be around 10%, reflecting historic management patterns and access to genetic services 10 . Currently, the likelihood that a genetic test will provide an IRD diagnosis is approximately 60% 11 .…”
Section: Introductionmentioning
confidence: 99%